Organisaatio Luhmannin autopoieettisen systeemiteorian mukaan tulkittuna - Hyyryläinen, Esa (Hallinnon tutkimuksen seura, 2024)
Organization interpreted according to Luhmann’s autopoietic systems theory The theory describes systems that reproduce their unity recursively through their own operations. This is autopoiesis. As social systems organizations consist solely of communication. A structural coupling allows the environment to affect the organization’s functioning. Openness of the organization is possible through its closure. Reproduction is based on the distinction the organization makes in relation to its environment. It does this by utilizing its own codes and decision-making programs. Coding is a prerequisite for information that affects events in organization. Organization’s decisions are events that link to past and future decisions. Coding is also a reduction of the complexity of the environment. Simultaneously the organization produces itself and maintains its autopoiesis. At the center of Luhmann’s theory is an organization that makes itself and adapts as part of its constantly changing environment. Often, this is an organization that copes with conflicting demands.
Keywords: organisaatio; autopoiesis; system; systems theory; systeemiteoria; fi=Julkisjohtaminen|en=Public Management|